Discrimination of zingiberaceae medicinal herbs Using analytical methods combined with chemometric techniques - Pauzi, Aslia Natasha (2022)
Zingiberaceae is one of the well-known families that are widely used as herbal medicines due to its various beneficial values. However, substitution with closely related species has become a serious issue in the herbal industry due to similarities in their physical appearance. Therefore, the development of a method for herbal discrimination is crucial to ensure its accurate identity and authenticity. This study aims to evaluate the ability and effectiveness of analytical methods that consist of Fourier Transform Infrared (FTIR) spectroscopy and electronic nose based on gas chromatography (e-nose-GC) combined with chemometric techniques to discriminate selected Malaysian medicinal herbs from the Zingiberaceae family. Nine powdered rhizomes of the Zingiberaceae family consisting of Alpinia conchigera, Alpinia galanga, Curcuma longa, Curcuma xanthorrhiza, Curcuma zedoaria, Kaempferia galanga, Kaempferia pandurata, Zingiber officinale and Zingiber zerumbet were used in this study. The best discrimination method was determined based on its accuracy percentage of discrimination performance. Results show that all samples were successfully discriminated against using both analytical methods with the aid of chemometric techniques. The best method was conducted by a combination of e-nose-GC and discriminant factor analysis (DFA) with an accuracy of 99.02 %, and followed by a combination of e-nose-GC and principal component analysis (PCA) with an accuracy of 98.17 %. In conclusion, the combination of FTIR spectra and e-nose-GC data with chemometric techniques can be applied for a rapid, accurate and reliable methods for the discrimination of medicinal herbs from the Zingiberaceae family as well as herbal authentication and quality control of herbal products.